2018
DOI: 10.3390/horticulturae4040029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Sulfur Dioxide Pads on Botrytis Mold in ‘Italia’ Table Grapes under Cold Storage

Abstract: ‘Italia’ grape is one of the most important table grape cultivars grown worldwide. Gray mold, caused by Botrytis cinerea Pers. Fr., is one of the most important causes of postharvest decay of table grapes, and the control of this disease is very difficult because postharvest treatments with synthetic fungicides are not allowed in many countries. The objective of this study was to compare different types of pads releasing different doses of SO2 during cold storage to control gray mold in ‘Italia’ table grapes g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
2
34
0
1
Order By: Relevance
“…Considering these aspects, combined with cold storage, the SO 2 -generating pads can be used as a tool to control the gray mold of 'BRS Isis' seedless grapes, at least for a period of 50 days. A similar performance has also been observed in rthe maximum reduction of the disease incidence of 'BRS Vitoria' and 'Italia' table grapes at 50 days of cold storage and at seven days at 22 ± 2 • C, respectively [17,22].…”
Section: Chemical Characteristics Of Grapessupporting
confidence: 74%
See 1 more Smart Citation
“…Considering these aspects, combined with cold storage, the SO 2 -generating pads can be used as a tool to control the gray mold of 'BRS Isis' seedless grapes, at least for a period of 50 days. A similar performance has also been observed in rthe maximum reduction of the disease incidence of 'BRS Vitoria' and 'Italia' table grapes at 50 days of cold storage and at seven days at 22 ± 2 • C, respectively [17,22].…”
Section: Chemical Characteristics Of Grapessupporting
confidence: 74%
“…Grapes were harvested at full ripeness when the content of the berry soluble solids reached around 14 • Brix [21,22]. Bunches were selected free from any disorders and standardized according to bunch shape, size, and mass, and subjected to the following treatments into a cold chamber at 1 ± 1 • C: (i) Control; (ii) SO 2 -generating pad; (iii) control with bunches inoculated with B. cinerea suspension; (iv) SO 2 -generating pad with bunches inoculated with B. cinerea suspension.…”
Section: Treatments and Storagementioning
confidence: 99%
“…On the other hand, despite emitting a constant amount of gas from the beginning to the end of the storage period, the slow release pad containing 7 g of a.i. did not lead to a complete absence of gray mold in the grapes, which can also be influenced by the natural occurrence of the fungus and the types of packaging employed [29][30][31]. The different plastic liners evaluated had no influence on this feature in the periods evaluated, however, it was found that the bunches submitted to a combination of factors displayed a lower mean incidence of gray mold compared to those in the additional treatment, which confirmed the need for SO 2 -generating pads in the control of gray mold of 'Benitaka' table grapes during cold storage [4].…”
Section: Natural Occurring Infection Of Gray Moldmentioning
confidence: 99%
“…As a postharvest treatment, the use of SO 2 -generating pads during cold storage is commercially implemented to manage gray mold of table grapes [11]. Dual release SO 2 generators inside the boxes have been commonly used for grape storage and transportation for periods up to two months [7,12,13]. Grape exporters are always worried about limited long-distance transport of fresh grapes, especially when intensive production occurs in subtropical areas where two crops per year is possible.…”
Section: Introductionmentioning
confidence: 99%